Identification and functional analysis of m6A in the mammary gland tissues of dairy goats at the early and peak lactation stages - Wang, Shujun; Zhang, Lu; Xuan, Rong; Li, Qing; Ji, Zhibin; Chao, Tianle; Wang, Jianmin; Zhang, Chunlan (Frontiers in Cell and Developmental Biology, 2022)
N6-methyladenosine (m6A) is the most common reversible epigenetic RNA modification in the mRNA of all higher eukaryotic organisms and plays an important role in the regulation of gene expression and cell function. In this study, m6A-modified methylated RNA immunoprecipitation sequencing (MeRIP-seq) and transcriptome sequencing (RNA-seq) were used to identify the key genes with m6A modification during mammary gland development and lactation in dairy goats. The results showed that m6A methylation occurred at 3,927 loci, which were significantly enriched in the 3′ untranslated region (3′UTR) and the termination codon region. In the early stage and peak stage of lactation, m6A methylation occurred extensively in mammary tissues, and a total of 725 differentially expressed m6A-modified genes were obtained, all negatively correlated with mRNA expression. In addition, Gene Ontology (GO) enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis showed that different methylated genes were mainly involved in the growth and apoptosis of mammary epithelial cells through signaling pathways, such as the mitogen-activated protein kinase (MAPK) and phospholipase D pathways, and then affected the development and lactation of mammary gland. All in all, we identified and analyzed the methylation events related to the development and lactation regulation of mammary gland at the early and peak lactation stages, and provided a theoretical basis to reveal the physiological regulatory system of mammary gland development and lactation in dairy goats.